2004
DOI: 10.1097/01.tp.0000100397.86756.a3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a human pancreatic islet-transplant program through a collaborative relationship with a remote islet-isolation center

Abstract: Collaboration with an experienced PIT/PII center allows developing programs to focus on patient safety and care, prudent use of pancreata, and consolidates PII expertise and experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 4 publications
1
49
0
1
Order By: Relevance
“…Currently, a vast majority of islet transplant procedures is performed in the ITA setting (6,(8)(9)(10)(11). This series shows that islet transplantation can be done in the IAK setting with equal efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a vast majority of islet transplant procedures is performed in the ITA setting (6,(8)(9)(10)(11). This series shows that islet transplantation can be done in the IAK setting with equal efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…In the steroid-free era, the effort has been concentrated on islet transplant alone (ITA), in nonuremic patients with metabolic lability (3,(6)(7)(8)(9)(10)(11). No study has specifically addressed the impact of a sirolimus-based, steroid-free immunosuppression regimen in a series of islet-after-kidney (IAK) transplantation so far.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to standardize shipping procedures, we have developed a protocol based on the use of gas-permeable bags (GPBs) that has been utilized in the ongoing clinical trials between the UM-ICPC and remote CITPs (6,7). Similar protocols have been recently adopted at other centers (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent trials have shown that the center's experience in islet isolation and patient management plays a critical role in the success rate of the CIT program (CITP) (1)(2)(3)(4)(5). The use of regional Islet Cell Processing Centers (ICPC), isolating islets that are sent to remote CITP, has proven successful in recent years both in Europe and United States (6)(7)(8)(9). The concept of ICPC-CITP networks may allow for better utilization of donor pancreata and to obtain a steady supply of high-quality islets, while containing the overall costs of establishing a new ICPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation